Development of the Implementation of the Implementation of the Leadership Style Mechanism in Optimizing the Performance Motivation of Office Boy and Security Guards - Junengsih Junengsih; Elda Sagitarius; Partimah Partimah; Annisa Frisca Fauziah (ProBisnis : Jurnal Manajemen, 2023)
The current individual phenomena reveal that performance is impossible to achieve maximum results if there is no motivation. The purpose of this study was to determine the analysis of the Application of Leadership Style and Motivation in improving the performance of Office Boy (OB) and Security Units (SATPAM). This study uses a qualitative method. The subjects used in the research were sources from the OB division and the Pertiwi Group Security Guard using primary data, namely interviews. The results of the study show that the Role of Leadership Style is successful in Improving the Performance and Performance Motivation of Office Boy and Security Guard Pertiwi Group Educational Institutions.